GE_GERICHTE C/21290/2017 vom 16. Januar 2018 - GE Cour de justice (2018)
MESURE PROVISIONNELLE ; CONCURRENCE DÉLOYALE ; COMPARAISON DES ACTIVITÉS ; IMITATION(PROPRIÉTÉ INTELLECTUELLE) | CPC.5.al1.letd; CPC.5.al2; CPC.261; CPC.267; CO.97; CO.160; CO.162; CP.292; LOJ.86; LCD.2; LCD.3.al1.lete